(Un)Ethical Leadership and Identity: What Did We Learn and Where Do We Go from Here? - Hunter, Samuel T. (2012)
The purpose of this article is to highlight and comment on the key findings emerging from the collective efforts of the special issue on leadership, ethics, and identity. Highlights include definitional advancements, processes comprising ethical leadership, as well as outcomes and moderating factors. In addition, I attempt to synthesize work across authors by identifying common themes as well as conflicting elements in the article. I conclude with a discussion on emerging areas in need of future research investigation in the leadership and ethics arena.
Keywords: Unethical; Summary; Ethics; Leadership